A Comparative analysis of the immature phase of polybagged plant and budded stump planted fields of Hevea - Joseph T; George K T; Jessy M D; Punnoose K I (Indian Journal of Natural Rubber Research, 2001)
The study analyses the commercial realisation of the experimentally proven difference in the duration of immature phase between polybagged plants and budded stumps of Hevea brasiliensis under smallholding conditions and its variations under different cultural practices. The database consisted of secondary information obtained from Rubber Plantation Development (RPD) files related to 1814 polybagged plant and 471 budded stump planted fields, collected from 23 regional offices of the Rubber Board located in Kerala, Tamil Nadu and Karnataka in India. The pattern of the adoption of major cultural practices in both categories was comparatively assessed. On an average, polybagged plant and budded stump planted fields reported a duration of immature phase of 6.99 and 7.19 years respectively and the difference (73 days) was statistically significant. However, it was found that the difference in duration of immature phase was not economically significant as fields of polybagged plants required an advantage of at least 150 days to realise an annuity equivalent to that of budded stump planted fields. But an assumed 2.6 per cent higher yield in the former gave an annuity equivalent to that of the latter fields. Hence the economic advantage of fields with polybagged plants may have to originate from the cumulative economic impact of shorter immature phase, lower vacancy, uniform establishment, higher tappability and higher yield rather than from shorter immaturity period alone.
Keywords: Budded stumps; Economic analysis; Hevea; Immaturity period; Planting material; Polybagged plants